Cultivar Diversity of Balsam (Impatiens balsamina L.) in Banyumas Regency - Rizki Aulia; Pudji Widodo; Wiwik Herawati (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Balsam or garden balsam (Impatiens balsamina L.) is a widely grown flowering plant belonging to the family Balsaminaceae. The most conspicuous part to distinguish the balsam is the difference in the flower shape and colors of each cultivar. The purpose of this research is to find out the cultivars diversity of the balsam. The method used in this study was survey with purposive sampling. The variables observed in this study was morphological characteristics including the stem, leaves, flowers, fruits, and seeds. The data obtained were analysed descriptively. The result of this study showed that there were 15 cultivars of I. Balsamina i.e. 'Pinkish White 5 Petal', 'Mix Pink Camellia, 'Pinkish White Camellia, 'Vivid Pink', 'White', 'Light Pink', 'Pinkish White', 'Light Magenta', 'Vivid Red', 'Red Camellia, 'Reddish Camellia, 'Rose Red Camellia, 'Vivid Magenta Camellia, 'Rose Green Camellia, and 'Vivid Pink Camellia’.